1976
DOI: 10.1007/bf01469249
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkungen einer langdauernden exogenen Gonadotropinzufuhr auf die testikul�re Insuffizienz bei Dauerdialysepatienten

Abstract: Thirtheen male patients with chronic renal failure undergoing regular dialysis treatment (2 X 8-10 hours/week) were treated with gonadotropins (HCG, Primogonyl) primarily 2 X 2,000 IU/week and later 2,000 IU/week. Before HCG administration and during 4-months HCG-therapy testosterone, dihydrotestosterone, Androstandiol, LH and FSH levels were determined by RIA-methods in 7-14 days intervals. Before HCG-application plasma testosterone levels were low and did not increase in the course of regular dialysis treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It is, therefore, not surprising that acute exogenous administration of human chorionic gonadotropin (hCG) is accompanied by a low testosterone response in dialysis patients (48,122,123). However, some authors have reported that prolonged HCG administration is followed by normalization in plasma testosterone levels, but that these levels decrease immediately after cessation of therapy or dose reduction to less than 2,000 IU HCG twice a week (123).…”
Section: Human Chorionic Gonadotropinmentioning
confidence: 99%
“…It is, therefore, not surprising that acute exogenous administration of human chorionic gonadotropin (hCG) is accompanied by a low testosterone response in dialysis patients (48,122,123). However, some authors have reported that prolonged HCG administration is followed by normalization in plasma testosterone levels, but that these levels decrease immediately after cessation of therapy or dose reduction to less than 2,000 IU HCG twice a week (123).…”
Section: Human Chorionic Gonadotropinmentioning
confidence: 99%
“…The elevation of basal levels of LHmuch more striking than for FSHappears, therefore, not necessarily correlated to a manifest damage of the Leydig cells. This is surprising since elevated levels of LH are probably the most consistent finding in dialyzed patients (Holdsworth et al -1977;Sy Lim and Fang -1975;Bundschu et al -1976;Hrubesch et al -1973;Bundschu et al -1974;Heinrichs et al -1974).…”
Section: Discussionmentioning
confidence: 98%
“…Introduction ment of the male gonads in patients maintained on hemodialysis (Holdsworth et al -1977;Sy Lim and Fang -1975;Bundschu et al 1976). Further, virtually all investigators have reported low plasma testosterone levels in these patients (Holdsworth et al -1977;Sy Lim and Fang -1975;Bundschu et al -1976;Hrubesch et al 1973;Guevara et al -1969;Chen et al -1970;Gupta et al -1975;Zadeh et al -1975;.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In view of raised LH levels in uremic man (Bundschu et al -1976) and uremic animals (Kreusser et alin press), the ultrastructural evidence of low basal Leydig cell activity, which can be restored by high doses of hCG, points to gonadal endorgan resistance in uremia. The concept of endorgan resistance was originally proposed on the basis of measurements of the interaction between LH and testosterone levels in uremic man (Bundschu et al -1976); this notion is also supported by recent findings in our laboratory that the dose-response-curve for testicular CAMP content in response to LH is shifted to the right in uremic animals (Kreusser et alin press). The finding in uremic animals of abnormal Sertoli cell ultrastructure which is partially responsive to hCG is compatible with inappropriately low local testosterone concentrations in uremic animals and these may be responsible for abnormal ultrastructure of the germinal epithelium.…”
Section: Alterations Of Leydig Cells During Uremiamentioning
confidence: 99%